Clinical quiz: a woman with mechanic’s hands - Jamani, Nurjasmine Aida; Sirol Aflah, Syazatul Syakirin (Oman Medical Specialty Board, 2021)
A 31 –year-old woman presents with shortness of breath on exertion for the past six months. The symptoms had progressively worsened for the past one month. She had an episode of chest infection prior to her visit in the clinic. She also complains of intermittent lower limb weakness with bilateral large joint pain leading to difficulty in ambulation. There were also intermittent episodes of non-specific joint pain of the hands and wrist associated with skin rash. She has no known medical illness.